Safety and Tolerability of KIO-101 Eye Drops in Healthy Volunteers and Patients with Ocular Surface Disease-A Phase I Study - Doreen Schmidl; Nikolaus Hommer; Martin Kallab; Andreas Schlatter; Clemens Nadvornik; Franz Obermayr; Stefan Sperl; Eric J. Daniels; Gerhard Garhöfer (MDPI AG, 2024)
Purpose: Inhibitors of dihydroorotate dehydrogenase (DHODH) have been found to be potent anti-inflammatory agents. Recently, a topical formulation (KIO-101 eye drops) of a DHODH inhibitor has been developed. The aim of the present study was to evaluate the safety and tolerability of KIO-101 eye drops in Healthy Volunteers (HVs) and patients with conjunctival hyperemia. Methods: The study was carried out in a double-masked, placebo-controlled, randomized, parallel-group design with two parts. In part I, HVs received single and multiple instillations (four times daily for 12 consecutive days) of KIO-101 eye drops in ascending doses of 0.05%, 0.15%, and 0.30%, respectively. Part II was conducted in patients with conjunctival hyperemia who received 0.15% KIO-101 eye drops twice daily for 12 consecutive days. Ophthalmic and systemic safety examinations were performed on all participants. In part II, ocular hyperemia grading and an ocular surface disease index (OSDI) questionnaire were performed. Results: 24 HVs participated in part I and 21 patients in part II. KIO-101 eye drops were well tolerated in all subjects. No serious adverse events (SAEs) occurred, and all AEs that were reported were transient and considered mild to moderate. In the highest dose cohort (0.30%), epistaxis occurred in two subjects after multiple instillations. In part II, after 12 days treatment with 0.15% KIO-101, conjunctival hyperemia decreased by −1.1 ± 0.27 points in the treatment and −0.6 ± 0.79 points in the placebo group (p = 0.0385). OSDI decreased from 47.9 ± 18.7 to 27.6 ± 19.13 points in the treatment group, while in the placebo group, a change from 41.3 ± 12.08 to 27.3 ± 18.63 points occurred. Conclusions: A 12-day treatment regimen with topical KIO-101 eye drops at low and mid doses was safe and well tolerated in both HVs and patients with conjunctival hyperemia. The obtained results point towards an early sign of reduction in conjunctival hyperemia.